Effect of loading frequency on the fatigue life in compression of natural hydraulic lime mortars. (April 2022) - Garijo, L.; Ortega, J.J.; Ruiz, G.; De La Rosa, Á.; Zhang, X.X.
Abstract: This paper focuses on the study of the influence of the loading frequency on the fatigue life in compression of natural hydraulic lime (NHL) mortars. For this purpose, fatigue tests were performed under three different loading frequencies: 0.05 Hz, 0.5 Hz, and 5 Hz. The maximum and minimum stresses applied in the fatigue tests were 85% and 20% of the compressive strength of the mortar, respectively, and the runout limit was set at around three days. It is observed that the NHL mortar is sensitive to the loading frequency; that is, for higher frequencies, more cycles are resisted by the specimens. Concerning the secondary strain of the fatigue creep curves, the Sparks and Menzies law was satisfied independently of the loading frequency. This law is useful to predict the number of cycles to failure of runouts if the secondary strain is known. In addition, given the high scatter of results, a probabilistic treatment is applied. Firstly, they were fitted to a two-parameter cumulative Weibull distribution function. Secondly, the results were fitted to a probabilistic fatigue model based on the initial distribution. With it, one can obtain the failure probability of the material for any given value of loading frequency. Finally, we observed an increase in the residual strength after fatigue in comparison to the static compression tests of around 40%. Through mercury intrusion porosimetry tests, it is concluded that a possible chemical curing of the material could have occurred induced by the cyclic loads. Highlights: Effect of loading frequency on fatigue to study cyclic loads of various intensities. NHL mortar sensitive to loading frequency; the higher it is, the more N . The Sparks and Menzies law is satisfied independently of the loading frequency. Adjustment to a 2-parameter Weibull distribution function and a probabilistic model. 40% increase of the residual strength comparing to the static compressive one.